ANTECEDENTS OF REVISIT INTENTIONS ON HOSPITAL CHOICE IN THE DEVELOPING COUNTRY: A SEM ANALYSIS - Shahabuddin, A. M.; Rahman, Mohammad Toufiqur; Ahsan, Syed Md Hasib; Islam, Md Shahidul; Akter, Kulsuma (American International Journal of Social Science Research, 2024)
In today's rapidly evolving healthcare landscape, understanding the factors that drive patient decision-making regarding hospital revisit intention is critical for hospitals to remain competitive and thrive. Despite the availability of world-class private hospitals, many patients from developing countries such as Bangladesh routinely travel beyond for medical treatment. Hence, developing countries are taking the initiative to strengthen their healthcare industries to increase GDP. This study aims to shed light on this issue by exploring the antecedents that affect hospitals in a developing country, Bangladesh. Data were collected by interviews at private hospitals in Chattrogram from November 2023 to December 2023 from 417 individuals using a randomized block design, and AMOS 24 was used for SEM analysis. The process in both EFA and CFA confirmed construct, convergent, and discriminant validity. The findings of this study demonstrate that the brand image of private hospitals affects patient revisit intent both directly and indirectly through service quality and patient satisfaction. A brand image does not influence the probability of returning to the same hospital. Moreover, commodity costs have a negative impact on revisit intention—service quality is associated with patient satisfaction which is moderated by the brand image of selected hospitals in Bangladesh. Management of hospitals can better position themselves to meet patients’ expectations, government may contribute to improve health outcomes and academicians may develop extensions of theory for the developing countries.  JEL Classification Codes: M1, M3, H51.